Well-Being, Psychological Capital, and Job Crafting as Determinants of Organizational Commitment among Narcotics Investigation Police Personnel - Rusmardi Rusmardi; Renil Septiano (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study examines the effects of well-being, psychological capital, and job crafting on organizational commitment among personnel of the Directorate of Narcotics Investigation of the West Sumatra Regional Police. The study employed a quantitative explanatory design using a survey method. The population consisted of all 49 personnel, and the study applied saturated sampling so that the entire population was included as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS 26. The results show that well-being has a positive and significant effect on organizational commitment, psychological capital also has a positive and significant effect and emerges as the strongest predictor, and job crafting has a positive and significant effect on organizational commitment. Simultaneously, the three variables significantly affect organizational commitment, with an Adjusted R Square value of 0.912. These findings indicate that organizational commitment in a high-pressure police unit is strengthened when employee well-being, psychological capital, and proactive work behavior are managed in an integrated manner.